Peran Inkubator Bisnis untuk Meningkatkan Minat Mahasiswa Menjadi Entrepreneur di Lingkungan Universitas Wiralodra Indramayu - Sonjaya, Nana Supriatna; Yudianto, Agus; Nurparatama, Meddy (Jurnal EMT KITA, 2025)
The role of business incubators is a strategic need for universities that offer entrepreneurship courses. This study examines the relationship between the role of business incubators and students' interest in starting a business. Based on statistical analysis, it was found that the existence of a business incubator has a significant positive effect on increasing students' interest in entrepreneurship. This finding suggests that the support provided by a business incubator can strengthen students' motivation to become entrepreneurs, especially in terms of access to mentors and resources that support business development. This study examines the relationship between the role of business incubators and students' interest in starting a business. Based on statistical analysis, it was found that the existence of a business incubator has a significant positive effect on increasing students' interest in entrepreneurship. This finding suggests that the support provided by a business incubator can strengthen students' motivation to become entrepreneurs, especially in terms of access to mentors and resources that support business development. The practical implications of this study are that educational institutions and business incubator managers can improve entrepreneurship support programs to encourage more students to explore and start their own businesses, by providing more structured facilities and mentoring. Observations show that the majority of students do not understand the business incubator at Wiralodra University. Currently, the development of business incubators can be an opportunity to run success in growing a successful and growing business in the future. It is not surprising that Wiralodra University students are interested in becoming entrepreneurs. The results of the correlation analysis show a very strong relationship (r = 0.937) between the role of business incubators and students' interest in starting a business. This figure is higher than the findings of a study by Johnson & Lee (2019), which recorded a correlation of 0.75 in a similar context, confirming that business incubator support can play a very significant role in increasing entrepreneurial interest. This finding supports the view put forward by several previous studies (eg, Smith, 2018) which identified business incubators as an important factor in encouraging student entrepreneurship. The role of business incubators on student interest has a contribution of 87.7% and other factors that were not studied contributed to this. The role of business incubators partially has a positive effect on student interest at Wiralodra University Indramayu. Simultaneously, the hypothesis states that the role of business incubators jointly influences student interest.
Keywords: Business Incubator; Student Interest; Entrepreneur